Campus connects: simplifying event booking for university life - Mohd Salehin, Nursyazwani Izzati (2025)
This project aims to develop a web-based event booking management system to make event management and registration is easier, especially in educational environments. The background study reveals the ineffective of traditional methods such as limited access to event, time consuming and difficulty to track event popularity and participate. The research question also guiding this project to align with the objective. This project will need internet access for registration and manage events since it is web application. The waterfall model has been used to make sure the structured approach through phase such as requirement analysis, system design, implementation, testing, deployment and maintenance. The system has features like to browse available event, register the event, cancel events, automation notification for upcoming event and give feedback for the complete events. For event organizer and administrator features are to manage events such as create event, edit events, delete events and can track student participations. This system also provides data analytics for event popularity that joint by student to help make decision in future planning. The benefit of this system is to improve event organization and better students’ engagement since it is centralized system. The system use technology for the frontend is HTML, CSS and JavaScript and for the backend are using language such as PHP for server-side, APIs and chart.js that will be used for data visualization. After the implementation, it will conduct usability testing to test the functional requirements and to make sure it will meet the user requirements and link with the existing system that has been evaluate.